Penerapan Model Pembelajaran Kooperatif Tipe Student Teams achievement Divisions (STAD) untuk Meningkatkan Hasil Belajar IPA Biologi Siswa Kelas VII.1 SMP Negeri 6 Dumai - Rogayah Hasan (Akademika: Jurnal Keagamaan dan Pendidikan, 2018)
The research focused on the implementation of cooperative learning student team’s achievement division (STAD) to improve students’ achievement in biology science of seventh grade at SMPN 6 Dumai. The research was conducted on August up to December 2015. The subject of the research was seventh grade students at SMPN 6 Dumai. There was 35 respondents included 15 males and 20 females. The research finding showed that the average absorption of students in daily test in first cycle is 68,6 (enough), on second cycle is increased 78,3 (good). The students’ learning completeness in first cycle was 74,3% and the second cycle was 97,1%. The average of students’ activity in first cycle is 90% (good) and second cycle is 100% (very good). Based on the finding, it can be concluded that the cooperative learning model student teams achievement division (STAD) can improve biology science students in learning outcomes of seventh grade at SMPN 6 Dumai.___________________Keywords: Teaching Creativities, Student Team’s Achievement Divisions